Diagnostic Precision of Computed Tomography (CT) Scan in Discriminating Perforated Appendicitis from Non-Perforated Cases - Khalid Mustafa; Uzma Azmatullah et al; Sara Zafar (ziauddin University, 2024)
Background: Acute appendicitis, when the appendiceal lumen is obstructed, leads to development of inflammation and eventually perforation. Pre-operative identification of ruptured appendix could help determine therapy, including consideration for a non-surgical approach towards management. Although, no doubt exists in the reliability of Computed tomography (CT) in detecting acute appendicitis (AA), however, its efficiency in discriminating the non perforated appendicitis from ruptured one still needs clarification. This study aimed to establish the diagnostic accuracy, sensitivity and specificity of CT scan in acute appendicitis in terms of the presence or absence of perforation. Methods:  A cross sectional study was conducted in the Department of Radiology, Dr. Ziauddin University Hospital, Karachi, for 6 months. Patients (171) clinically suspected of appendicitis were included in this study. CT was performed with oral and intravenous contrast administration and findings were documented. The final diagnosis was based on post-appendectomy histopathological analysis. Results: In the current study, computed tomography used for the detection of perforated appendicitis had 79.07% sensitivity, 89.06% specificity, 70.8% positive predictive value and 92.7% negative predictive value along with 86.5% accuracy, respectively. The precision of CT in the detection of ruptured appendicitis was 90.9% for female cases and 83.8% for male cases. Similarly, with respect to age, furthermore, CT precision was 85.59% for ≤ 30 years of age and 88.68% for > 30 years of age (p=0.0005). Conclusion:  The computed tomography (CT) scan is a non-invasive investigation with high precision and can be used confidently to select cases with non-perforated appendicitis for initial non-operative management. ​​Keywords: Perforated Appendicitis; Computed Tomography; Appendectomy.